Tfn Brownie / Putri Nabila Mustafa Kamal - Mustafa Kamal, Putri Nabila (2021)
Tfn Brownie is a unique brownie because it is crispy and thinnest brownie which is different from typical cake we used to eat. There are 4 flavour of Tfn Brownie have been produced for this business which is Chocolate Chip, Mint, Red Velvet and Walnut. It comes in different taste where customers can choose based on their likes. As for the prices, it is very affordable for each flavour because customers can get only at RM15. All flavour is same price, none of it have different price to make sure customers loyal with Tfn Brownie. The targeted customers are for anyone regardless of age. From 10 years old and above is edible to eat Tfn Brownie since it contained nutritious ingredients and suitable to eat while breakfast, lunch, tea time or dinner depends on their mood. The chocolate chip flavour and red velvet is highly demanded because of the premium chocolate has been used while produced it. Tfn Brownie always make an offer such as free postage and get free items to gain customers’ interest in the product. By doing this, Tfn Brownie always received order everyday by different location. Next, the platform for this online business is Facebook and WhatsApp because it is very easy to customers since these platforms are very popular among them. Thus, it is very useful with a lot of features to attract customers and gain more sales at one. Therefore, by creating this brand “Tfn Brownie”, I believe it can go further to expand as the business keeps growing day by day because of the satisfaction of the taste from the customers.